(Re)Presenting the role of iconography in African Christian liturgy: A case study of Serima Mission in the Catholic Diocese of Gweru in Zimbabwe (1948–2021) - Mudyiwa, Misheck (HTS teologiese studies, 2021)
This article examines the role of iconography in African Christian liturgy with a particular focus on Serima Mission in the now Catholic Diocese of Gweru in Central Zimbabwe. Of all Catholic missions in Zimbabwe, Serima Mission is perhaps the most popular in iconography with innumerable sets of wood and stone carvings portraying mostly religious scenes based on African designs and patterns. The atmosphere at Serima Mission, particularly the church interior, presents an expression of the power of African art, visual language, summation of the Catholic faith, and the otherness and transcendental nature of the omniscient, omnipotent, and omnibenevolent Christian God. This article firstly presents the history and impact of Serima African School of iconography under the tutelage of Fr John Groeber. Furthermore, it explores the role of iconography in African Christian liturgy on the Roman Catholic Church. The article critically examines iconography in African religion and spirituality, Sacred Scripture and celebrated traditional Christian practices. This article argues that, whilst religious symbols are on the physical realm, in reality, they symbolise and represent the metaphysical and transcendental realities. Although, they are often associated with religious formalism, exaggerated spirituality, and idol worship, icons and images have conveyed unprecedented allegorical messages across time and cultures.Contribution: This article expands the studies of iconography and semiology in theological landscapes and texts, allowing for the recognition and repositioning of art interpretation from an African experience.